2001
DOI: 10.1038/sj.bmt.1703062
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of receptors for thyroid hormone and insulin-like growth factor-1 during reconstitution after allogeneic hematopoietic stem cell transplantation

Abstract: Summary:Treatment with neuroendocrine hormones has been suggested to promote reconstitution of the immune system after hematopoietic stem cell transplantation (HSCT). We investigated the expression of genes encoding receptors for growth hormone (GH), insulin-like growth factor-1 (IGF-1) and triiodothyronine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Total RNA was isolated from 1 × 10 6 MNC using an RNeasy Mini Kit (Qiagen Inc., Valencia, CA, USA) according to the manufacturer's protocol. TR genes were assessed by a semi‐quantitative PCR as described (Omazic et al . 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from 1 × 10 6 MNC using an RNeasy Mini Kit (Qiagen Inc., Valencia, CA, USA) according to the manufacturer's protocol. TR genes were assessed by a semi‐quantitative PCR as described (Omazic et al . 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, treatment with neuroendocrine hormones has been suggested to improve reconstitution of the immune system after haematopoietic stem cell transplantation, whereas the mechanisms involved in THs action in haematopoiesis still remain unclear (Omazic et al . 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This finding correlates with previous results from our group and from other studies. (Kauppila et al, 1998;Munker et al, 2001;Omazic et al, 2001) In our study, all patients were given cyclosporine A as GVHD prophylaxis after HSCT. Cyclosporine A is known to mainly affect T lymphocytes by inhibiting intracellular signals involving calcineurin.…”
Section: Discussionmentioning
confidence: 98%
“…(Johnson et al, 1992;Walsh and O'Connor, 2000) We have previously demonstrated a reduced expression of RNA for IGF-1R in lymphocytes from patients undergoing HSCT. In our study, samples were collected at 6 weeks, 2 and 3 months after HSCT (Omazic et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In human early hematopoietic cells, THs might play a significant action in the regulation of the growth (Gruber et al, 1999;Grymuła et al, 2007;Kawa et al, 2010). More importantly, the genomic and nongenomic actions of THs might be regulated these mechanisms (Gruber et al, 1999;Milne et al, 1999;Dorshkind and Horseman, 2000;Porter and Mandel, 2000;Bauer et al, 2001;Omazic et al, 2001;Marongiu et al, 2004;Kawa et al, 2010;Barreiro Arcos et al, 2011;Franchini et al, 2011;Kandir and Keskin, 2016). In addition, Kawa et al (2010) reported that any change in the gene expressions of thyroid receptors (TRs; α and β) might change the hematopoietic progenitors.…”
Section: Short Communicationmentioning
confidence: 99%